2012
DOI: 10.1111/j.1745-4603.2012.00347.x
|View full text |Cite
|
Sign up to set email alerts
|

Texture Perception Determined by Soy Protein Isolate and Inulin Addition in Potato Puree: Links With Mechanical and Microstructural Features

Abstract: KEYWORDSFlow behavior, long-chain inulin, microstructure, soy protein isolate, texture perception, trained and untrained panel 4 Corresponding ABSTRACTThis study evaluated the effect of adding soy protein isolate (SPI) and long-chain inulin (INL) blends with 10 different SPI : INL ratios on the textural, rheological and microstructural properties of freshly made and frozen/thawed potato puree. All the potato puree samples were subjected to a sensory texture profile analysis and a trained panel rated the inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 30 publications
(52 reference statements)
0
8
0
Order By: Relevance
“…The amount of each ingredient, either alone or in blends, that could be added to the PP control was based in previous studies (Alvarez et al . ,b, ). Code samples and composition of the seven PPs studied are presented in Table .…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The amount of each ingredient, either alone or in blends, that could be added to the PP control was based in previous studies (Alvarez et al . ,b, ). Code samples and composition of the seven PPs studied are presented in Table .…”
Section: Methodsmentioning
confidence: 99%
“…In each methodology, the seven PPs were served in white plastic vessels, coded with a three‐digit number, at a temperature of 55 ± 1C, as previous studies showed that this is the preferred temperature for PP consumption (Alvarez et al . ,b, ). After thawing, samples were brought up to 55C and kept at this temperature by placing them in a Hetofrig CB60VS water bath (Heto Lab Equipment A/S, BirkerØd, Denmark) prior to tasting, where water and product temperatures were monitored by T‐type thermocouples.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations